KOMPARASI KONSEP WALI NIKAH MENURUT SHAFI’IYAH DAN HANAFIYAH - Edi Susilo (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2015)
Abstract: Marriage is a strong bond that is described in al-Qur’an as mithaqan ghalizan, an extraordinary bond (solemn pact). Therefore, to reach the validity of marital contract, there are some requirements to fulfill. Among the Muslim scholars of the Islamic thoughts, they all agree to the requirements of the validity of marital contract required but one. It is about a guardian of marriage for woman. Among Syafi’iyyah Islamic thought, a guardian of marriage for woman is an absolute requirement that must be met for the sake of a validity of marriage. While Hanafiyyah Islamic thought, they consider that a guardian of marriage is only recommended and is not the condition to be met. This difference of opinion, of course, cannot be separated from the legal sources they use, the legal reasoning methodology, and their understanding of which. Based on a further elaboration, there are some similarities and differences between Syafi’iyyah and Hanafiyyah scholars’ point of view as are going to be discussed in this article.Abstrak: Pernikahan adalah ikatan yang kuat yang dijelaskan dalam al-Qur'an sebagai ghalizan mithaqan, ikatan yang luar biasa. Oleh karena itu, untuk mencapai validitas kontrak perkawinan, ada beberapa persyaratan untuk memenuhi. Di antara para ulama Muslim dari pemikiran Islam, mereka semua setuju dengan persyaratan keabsahan kontrak perkawinan, yaitu wali nikah bagi seorang wanita. Di antara pendapat Syafi'iyyah, wali nikah bagi wanita merupakan syarat mutlak yang harus dipenuhi demi validitas perkawinan. Sementara menurut Hanafiah, mereka menganggap bahwa wali nikah hanya direkomendasikan dan tidak yang harus dipenuhi. Perbedaan pendapat ini, tentu saja tidak dapat dipisahkan dari sumber-sumber hukum yang mereka gunakan, metodologi pertimbangan hukum, dan pemahaman mereka yang. Berdasarkan penjabaran lebih lanjut, ada beberapa kesamaan dan perbedaan antara titik Syafi'iyyah dan Hanafiyah 'pandang sebagaimana yang akan dibahas dalam artikel ini.Kata Kunci: